METHOD OF LOCAL ADRENAL ORGAN-PRESERVING CRYOLYSIS. EXPERIMENTAL STUDY - O. S. Popov; V. E. Gyunther; G. Ts. Dambaev; V. R. Latypov; R. Ya. Geydarov; A. N. Galyan (Бюллетень сибирской медицины)
A method of local adrenal organ-preserving cryolysis using a porous nickelide titanium cryoprobe created for this purpose was developed in experiments in 14 dogs. The efficacy of the method was demonstrated by the morphological evidence and hormone tests.